La construction médiatique et la multiplicité événementielle - Farhat El Khoury (Communication)
Events are intimately linked to their mediatization. Raw facts exist with or without the media but are only transformed into events by the media — a process shaped by multiple political references and the media players involved. This article examines what we will call event multiplicity, using the example of the televised reporting of the car bomb that went off in Beyrouth on July 9, 2013. In analyzing the broadcasts of two local TV stations, the author observes that for a single explosion, there were many events.